THE USE OF SYMBOLIC IMAGES IN ABDUQAYUM YULDOSH’S STORIES (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the issue of symbolism in the stories of writer Abduqayum Yuldoshev. Also, the system of images and the artistic function of symbolic images in the writer’s stories are also researched.